Psikoedukasi: Meningkatkan Peran Orangtua Dalam Mendidik Anak Pada Setting Pendidikan Inklusi - Komarudin; Winarsih, Tri (LPPM IST AKPRIND Yogyakarta, 2021)
This article describes the results of community service activities. This program aims to increase the knowledge and role of guardians in educating children in inclusive education settings by understanding and accepting whatever the child's condition, and providing social support according to the responsibilities of parents. The method used in this community service program is psycoeducation. The stages include: 1) preparation (licensing, consolidation with objectives, preparation of materials, preparation of tools and materials / preparation of training modules and procurement of learning media), 2) the implementation of training for 2 meetings offline and online, 3) evaluation of activities. The result of this program is an increase in the understanding of the parents that their children are attending schools that provide inclusive education, the guardians of students understand better how to care for and educate children, especially in terms of mentoring Learning. This increased understanding also makes parents more concerned and provides social and emotional support to their children with special needs.